Mechanisms of gut microbiota-mediated bone remodeling. (2nd January 2018) - Yan, Jing; Takakura, Ayumi; Zandi-Nejad, Kambiz; Charles, Julia F.
ABSTRACT: The mechanisms underlying the systemic effects mediated by gut microbiota are under active investigation. In addition to local, direct effects of gut microbiota on the host, metabolic products from microbiota may act peripherally, reaching distal organs through the circulation. In our recent publication we demonstrated that gut microbiota influence bone remodeling distally, promoting both bone resorption and formation. We proposed that these effects are mediated, at least in part, by the induction of insulin like growth factor (IGF-1) by the microbiota metabolite short chain fatty acids (SCFA). Here we explore additional mechanisms by which microbial metabolites could directly or indirectly alter host bone remodeling. We discuss whether SCFA directly modulate bone resorption by their actions on osteoclasts, and test the possibility that serotonin is another gut microbiota derived long-distance mediator of effects on bone remodeling. A detailed understanding of the mechanisms of microbiota effect on bone remodeling could help establish potential therapeutic strategies to promote bone health.